Statistical methods - Mills, Frederick C. (London : Sir Isaac Pitman & Sons, Ltd., 1955)
In preparing the third edition of this book, the author has extended and brought up to date examples of the uses of statistics in research and administration. Also, this text has been made a more effective instrument for instruction in the logic and methodology of modern statistics, and a more useful handbook for the practicing statistician.
Previous editions published under title: Statistical methods applied to economics and business.
Includes index.
Includes bibliographical references: p. 821-830.
ne 3/04/2018
Loans
Keywords: Statistics; Economics; Business